Formação continuada de professores ribeirinhos em uma escola do Rio Mamuru, no município de Juruti - Pará: desafios e perspectivas - Santos, Adriano Fernandes dos (Brasil, 2023)
This article entitled “Continuing training of teachers in a school on the Mamuru River, in the Municipality of Juruti - Pará: challenges and perspectives” aimed to investigate how the continuing training of teachers from the 1st to the 5th year of elementary school takes place for the development of practice teacher at a school on the Mamuru River, in the municipality of Juruti - Pará, highlighting the challenges and perspectives of teachers who work in this location. Specifically, we aim to understand how the continuing education of teachers at a school in Rio Mamuru takes place and to analyze the main challenges faced by teachers and what their perspectives are. The study is a field and bibliographic research with a qualitative approach. For data collection, an open questionnaire was applied to 3 teachers from the Mamuru river school. The study was based on national and international authors such as Arroyo (2005, 2008, 2012), Nóvoa (2009, 2022), Freire (2013), Romanowski (2009) among others that make up the work. The results of the analyzes carried out indicate the need to expand and raise the quality of continuing education for riverside education professionals, as according to the analyzed questionnaires, it was observed that there is an absence of face-to-face training actions aimed at rural teachers, as a public policy. Keywords: Mamuru River School. Continuing training. Teaching Practice. Riverside.